Laparoscopy training in Belgium: results from a nationwide survey, in urology, gynecology, and general surgery residents - De Win G; Everaerts W; De Ridder D; Peeraer G (Advances in Medical Education and Practice, 2015)
Gunter De Win,1,2 Wouter Everaerts,3,4 Dirk De Ridder,3 Griet Peeraer2 1Department of Urology, University Hospital Antwerp, 2Faculty of Medicine, University of Antwerp, Antwerp, Belgium; 3Department of Development and Regeneration, KU Leuven, Leuven, Belgium; 4Department of Urology, Royal Melbourne Hospital, Melbourne, VIC, Australia Background: The purpose of this study was to investigate the exposure of Belgian residents in urology, general surgery, and gynecology to laparoscopic surgery and to training of laparoscopic skills in dedicated training facilities.Methods: Three similar specialty-specific questionnaires were used to interrogate trainees in urology, general surgery, and gynecology about their exposure to laparoscopic procedures, their acquired laparoscopic experience, training patterns, training facilities, and motivation. Residents were contacted via their Belgian specialist training organization, using Survey Monkey as an online survey tool. Data were analyzed with descriptive statistics.Results: The global response rate was 58%. Only 28.8% of gynecology respondents, 26.9% of urology respondents, and 52.2% of general surgery respondents felt they would be able to perform laparoscopy once they had finished their training. A total 47% of urology respondents, 66.7% of general surgery respondents, and 69.2% of gynecology respondents had a surgical skills lab that included laparoscopy within their training hospital or university. Most training programs did not follow the current evidence about proficiency-based structured simulation training with deliberate practice.Conclusion: Belgian resident training facilities for laparoscopic surgery should be optimized. Keywords: simulation, questionnaire, resident education, minimal invasive surgery training, surgical case load, implementation of laparoscopy training